Unusual Presentation of Thelazia callipaeda in the Anterior Chamber of a Human Eye - Singh, Sweta; Piya, Saurav; Gurung, Jeena; Raut, Shristi (Med Phoenix, 2023)
Introduction: We presented a 53 years old female with redness and pain of right eye for the past 3 months. Slit-lamp biomicroscopy revealed circumciliary congestion with a mobile, curved, white, rod-shaped parasite in the anterior chamber (AC) on the inferior surface of iris. For definitive diagnosis and management, we removed the parasite from the AC through limbal incision. Microbiological examination identified “Thelazia callipaeda”. Thelazia callipaeda is usually detected in the conjunctival sac and lacrimal sac. However, in this case from Lumbini Eye Institute and research centre, Western Nepal, the parasite was found in the anterior chamber of a human eye which is an unusual location.